TAHTA KEABADIAN: PENEMPATAN MAKAM RAJA-RAJA INDRAGIRI KOMPLEK KOTA LAMA DITINJAU DARI ANALISIS STRUKTURALIS SOSIAL - Kurnia Tirta (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
The king in a component of the community of adherent in the monarchy or power is in the highest ranks among other social classes of society. Its position is recognized by the supporting community in legal, political, social and even in the religious terms. A king, in his life cycle from birth, common sense, marriage to death is always characterized by rituals and ceremonials that are sacred, both in his living or in the power of his government, until after his death a king still occupies the highest social structure, in charge of his followers and servants. Many of kings’ tombs were magnificent built with great ornaments. The location of placement is also adjusted to a special position. This phenomenon was also seen in the tombs of the king Indragiri, Riau which places the tombs of the kings of Indragiri were in a special location, adjusted to the tombs position of the courtiers and visitors. This phenomenon raises two research questions; What is the position of the tomb placement of Indragiri kings in several cemetery complexes of the Indragiri kings of Riau? How is the structure of the tomb placement of Indragiri kings associated with the tombs of courtiers and their followers? As far as the methodology used to answer research questions was used archeological methodology which consists of several stages; collecting data, analyzing data, and interpreting data. Structural theorist Levis Starus was used as a foundation to uncover the structure of the king's tomb placement with the tombs of courtiers and followers. Temporary hypotheses showed that the placement of the Indragiri kings tombs were positioned at a central point surrounded by courtiers and followers according to their respective positions